Cross Infectivity Study of Four Subspecies of Oncomelania hupensis in Four Geographical Strains of Schistosoma Japonicum - M. Sudomo (Institute for Research and Community Services (LPPM) ITB, 1983)
Abstract. Four subspecies of Oncomelania hupensis, namely O.h.lindoensis, O.h.hupensis, O.h.nosophora and O.h.quadrasi were exposed to miracidia of four different geographical strains of Schistosoma japonicum, i.e.: the Chinese, Japanese, Philippine and lndonesian strains. Result of this experiments showed that O.h.lindoensis from Indonesia and O.h.hupensis from China found to be the most susceptible for all geographical strains of S.japonicum while O.h.quarasi from the Philippines was the most refractory and could only be infected with the Philippine strain. Sari. Empat subspecies Oncomelania hupensis: O.h. lindoensis, O.h. hupensis, O.h. nosophora, dan O.h. quadrasi telah dicoba diinfeksikan di dalam laboratorium dengan miracidia dan berbagai strain Schistosoma japonicum. Strain S. japonicum yang dipakai untuk menginfeksi keempat subspecies O. hupensis tersebut adalah strain Cina, Jepang, Filipina dan Indonesia sendiri. Hasil percobaan ini menunjukkan bahwa O.h. lindoensis dari Indonesia dan O.h. hupensis dari Cina ternyata paling tidak rentan dan hanya dapat diinfeksi oleh S. japonicum dari strain Filipina sendiri.